REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD DEVELOPMENT AND VALIDATION FOR THE QUANTIFICATION OF SUGAMMADEX IN BULK AND PHARMACEUTICAL DOSAGE FORM - BHAVYA SRI K; SRIJA G (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objective:A reproducible, precise, accurate method was developed for the analysis of Sugammadex in pharmaceutical dosage form and bulk, using RP-HPLC. This method is established in compliance with ICH guidelines Q2R1. Method:The method development and method validation of Sugammadex was performed usingthe instrument, SHIMADZULC- 20 AD pumps with SPD- 20A UV detector. A Phenomenex C18 250mm × 4.6mm × 5µm column was employed with detection wavelength of 210 nm. Results: The method validation was performed in accordance with ICH Q2 R(1) guidelines where the calibration curve was found to be linearwith r2as 0.9993. The LOD and LOQ were found to be 0.03784µg/ml and 0.114667µg/ml respectively.The %RSD of theprecision wasobserved to be in limits (≤2%). Conclusion:All validation parameters, including linearity, range, detection limit, quantification limit, precision, and accuracy, were examined and found to be within the specified limits in accordance with ICH recommendations Q2 (R1). In view of this, adopting this approach for routine quality control tests of both pure and pharmaceutical formulation can be done with ease.